Strength of graphene grain boundaries under arbitrary in-plane tension. (February 2019) - Fox, Andy; Ray, Upamanyu; Li, Teng
Abstract: Understanding the tensile strength of graphene grain boundaries (GBs) is crucial for correlating the mechanical properties of two dimensional polycrystalline graphene with its atomic defect structure, a key to the success of large area graphene in many promising applications. Existing modeling studies mainly focus on the deformation and fracture of graphene GBs under tension that is perpendicular to the GBs. In reality, however, when a polycrystalline graphene is subject to a simple tension, random distribution of GBs in the graphene leads to arbitrary in-plane loading conditions of the GBs that cannot be fully understood with existing knowledge. To this end, we carry out systematic molecular dynamics (MD) simulations and also delineate a continuum mechanics model to investigate the failure strength of graphene GBs under tension in all possible loading directions. Particular focus is placed on quantitatively deciphering the interplay between GB misorientation angle and loading angle, and their effects on the failure strength of graphene GBs. Prediction from the continuum mechanics model based on a disclination dipole theory agrees well with the results from MD simulations. In this sense, the present study offers important insights on a better understanding of the mechanical properties of large area polycrystalline graphene. Graphical abstract: Image 1